E-LEARNING SEBAGAI MEDIA PEMBELAJARAN: (Studi Kasus : STBA TECHNOCRAT TANGERANG) - Linda Apriyanti; Surdi Supriyadi; Yus Jayusman (LPPM STMIK BANDUNG, 2021)
The implementation of e-learning learning helps students to facilitate the learning processif they cannot attend class. STBA Technocrat has not used e-learning in the use of technology forlearning media.Some of the lecturers and students at STBA Technocrat are mostly private employees.Therefore the creation of e-learning is for learning media. To achieve these objectives the authoruses a research method approach, namely field studies and literature studies and the developmentand design of systems with the waterfall and UML models. Using PHP and MySQL programminglanguages. The conclusion is that with e-learning it can help facilitate lecturers and students indelivering and receiving material so that the teaching and learning process runs quickly not affectedby place and time.Keywords :E-Learning, Waterfall, UML, PHP, MySQL